Investment Opportunities and Tourism Business Development in The Village of Siallagan Village, Batak Adat Village - I Wayan Ruspendi Junaedi; Dermawan Waruwu; I Made Sumartana; Budi Hidajat; Irawan Irawan; Phuong Nguyen; Chanrith Ngin (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2023)
Siallagan Village is a traditional Batak village located in Samosir Regency, North Sumatra Province, Indonesia. The village has great potential for tourism business development thanks to its rich Batak culture and interesting historical sites such as the Court Chair Stone. However, this potential has not been fully exploited. This study aims to analyze investment opportunities and tourism business development in Siallagan Village, which is located in the middle of Lake Toba, North Sumatra. The research method used is field surveys, interviews with relevant stakeholders, as well as analysis of secondary data such as tourism statistical reports and economic information. This research identifies the key factors that support investment opportunities and tourism business development in Siallagan Village. First, the natural beauty of Siallagan Village, including white sand beaches, spectacular waterfalls and stunning mountain views, attracts both local and international tourists. Second, the rich and unique cultural heritage, such as traditions of music, dance and distinctive handicrafts, is the main attraction. Third, the large economic potential in the tourism industry can create job opportunities and increase regional income with proper infrastructure development. The results of this study are expected to provide insight for the government, investors and tourism entrepreneurs about the potential and opportunities that exist in Siallagan Village. This research also underlines the importance of sustainable development and environmental preservation in developing a tourism business on this island. In conclusion, Siallagan Village has promising investment opportunities and tourism business development. By exploiting the existing natural, cultural and economic potentials, as well as by adopting the right development strategy, this island can become a major tourism destination that provides significant economic and social benefits.